Spatialization of political action applied to waterways management an overview of Parisian urban small rivers - Carré, Catherine; Haghe, Jean-Paul (Environnement urbain / Urban Environment)

(untitled) (Réseau Villes Régions Monde, 2013)
The small urban rivers of the Paris conurbation are subject to local land use and segmentation processes at the threshold between urban politics and environmental policy. At present, the obligation to restore these streams pursuant to the Water Framework Directive is challenging stakeholders to proceed as collectively as possibly in this undertaking. This article attempts to identify the points of agreement and disagreement within a shared representation of local decision-makers’ relations with waterways through several spatiotemporal trajectories that are specific to each small river. We will show that the shared management of a river involves the management of not only the resource but also of a shared space. Choosing to model the relation between local societies and their river in time and space around a land-based diagram provides local and regional authorities with an explanation of their interactions with the river and its environments and can foster their capacity to act cohesively.